Using Native Woody Plants for Phytomanagement of Urban Technosols Contaminated by Wood Pole Preservatives - Heine, Philippe; Yavari, Sara; Frenette‐Dussault, Cédric; Zagury, Gérald J.; Brisson, Jacques; Labrecque, Michel (Clean : soil, air, water, 2021)
Technosols are a major component of urban areas with little to no value, but many benefits can be gained by the use of native plants for their ecological reclamation. The aim of this study is to examine the capacity of North American native woody species to establish in and remediate a wood preservative‐contaminated technosol. Nine species are planted in mesocosms containing highly contaminated or non‐contaminated synthetic technosols. Remediation potential and plant physiology parameters (survival, photosynthesis and root growth) are monitored during one growing season. Results show an inverse relation between species performance ranking in the non‐contaminated technosol compared to ranking in contaminated soil. Overall, Salix bebbiana and Sambucus canadensis show good potential for phytomanagement of heterogenous contaminated technosols, offering the best compromise between performance in non‐contaminated and contaminated soils. Most species are able to phytoextract copper (Cu), with Rhus typhina, Alnus crispa, and S. bebbiana showing the highest Cu concentrations in stems. The use of multiple native species for technosol reclamation can be beneficial due to the heterogeneous nature of soil contaminants. The potential of nine native North American woody plant species to remediate technosol is tested in a mesocosm experiment. There is an inverse relation between species’ performance ranking in the non‐contaminated technosol compared to their ranking in the contaminated soil. The use of multiple native species for technosol reclamation can be beneficial due to the heterogeneous nature of soil contamination.